Tic disorder in allergic rhinitis children and adolescents: a case-control study - Hossein Esmaeilzadeh; Mohammad Reza Yousefi; Negar Mortazavi; Mohammad Amin Gholami; Mohebat Vali; Seyed Ali Dastgheib (BMC Pediatrics, 2024)
Abstract Background Allergic rhinitis is the most common allergic disease. It can accompany psychological disorders such as tic disorders due to the prolonged course of the symptoms of allergic rhinitis. This pioneer case-control study aims to investigate tic disorders in children and adolescents under 18 years of age diagnosed with allergic rhinitis. Method The case group in this study consisted of patients who had both allergic rhinitis and tic disorders. Patients with allergic rhinitis without tic disorders were also enrolled as the control group with matched gender and age. Demographic characteristics, tic classifications, and contributing factors for allergic rhinitis and tic disorders were studied among the cases. Tic disorders were evaluated using DSM-5 criteria for the classification of tic disorders. Results 47 patients in the case group and 47 patients in the control group were included in this study. 53.2% and 46.8% were males and females in the case group, respectively. The mean age of the patients was 10.46 ± 3.97 years old. Sound tics were more common among the patients compared to motor tics. Patients with concomitant AR and tic disorders had more days per week with AR symptoms (P-value ≤ 0.001; OR (every day vs. three days a week = 11.02(2.98, 40.76))). Most patients with sound tick were women (p: 0.026), and most patients with motion tic were in the Provisional tic disorder group (p: 0.001). The history of infantile eczema was seen more in patients without sound tic (p: 0.025), and otitis media was significantly less common among patients with sound tics (p: 0.026). Provisional tic disorder was the most common class among the patients. In the case group (coexistence between allergic rhinitis and tic) compared to the control group, patients had significantly more days with AR symptoms per week. Conclusion This preliminary study indicates that Provisional tic disorder was the most common classification of tic among patients with allergic rhinitis, especially in patients with motor tics. Asthma in motor tics, a history of food allergy in infancy, and a history of infantile eczema were also common among patients with vocal tics. Also, patients with allergic rhinitis and tic had more severe disease (more symptoms per week) than those with rhinitis alone. These findings emphasize the association of tic disorders with immunological pathways.